Potential Application in Energy Harvesting of Intermodal Energy Exchange in a Frame: FEM Analysis - Iliuk, Itamar; Rebello da Fonseca Brasil, Reyolando Manoel Lopes; Balthazar, Jose Manoel [UNESP]; Tusset, Angelo Marcelo; Piccirillo, Vinicius; Castilho Piqueira, Jose Roberto (World Scientific Publ Co Pte Ltd, 2014)
This paper presents a Finite Element Analysis (FEA) of modal energy exchange and harvesting in a simple portal frame structure. We consider both horizontal and vertical support excitations resonant first with the first mode (sway mode) and latter with the second mode (the first symmetrical mode). As 2:1 internal resonance is present between these two modes, the phenomena of mode saturation and energy exchange (modal coupling) may occur. Thus, energy pumped into the system through one of the modes, is partially transferred to the other mode, not directly excited. An evaluation of the energy available for harvesting in each of the considered mode is computed.
Keywords: Energy harvesting; finite elements; modal saturation; modal coupling